TEACHER’S METHODS IN TEACHING INTEGRATED LISTENING AND SPEAKING AT ENGLISH DEPARTMENT - Febiola Mutri Ayuningtyas; Sri Wiyanah (Universitas Muhammadiyah Tangerang, 2023)
Teaching integrated listening and speaking has become crucial part of the curriculum. It helps leaners to communicate effectively and become more confident in learning. Therefore, it is essential for teacher to use the appropriate method when teaching these skills. The research purposes were to describe the teacher’s’ method in teaching integrated listening and speaking at English department and find students’ perception toward it. This study used qualitative method. It employed observation, interview, and documentation as a data collecting instrument. The research subjects were one teacher and four students of fourth semester in English department at Universitas PGRI Yogyakarta. The findings showed that teacher used post-method to teach integrated listening and speaking. The method indicated more flexible and can accommodate the students’ needs. The student’s perception towards the teacher’s method was positive due to students’ feeling of growing pleasure, interesting process and suitable method to easily learn by using Post-method.